2010
DOI: 10.1080/07315724.2010.10719882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumption of a Fermented Dairy Product Containing the Probiotic Lactobacillus casei DN-114 001 on Common Respiratory and Gastrointestinal Infections in Shift Workers in a Randomized Controlled Trial

Abstract: The results indicate that daily consumption of a fermented dairy product containing Lactobacillus casei DN-114 001 could reduce the risk of common infections in stressed individuals such as shift workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(139 citation statements)
references
References 44 publications
0
133
0
5
Order By: Relevance
“…Double-blind RCTs (DBRCTs) of this strain reported beneficial effects both in children (638 children, 3 --6 years old in daycare/schools, the incidence rate for CIDs in probiotic group [0.0782] was 19% lower than the control group [0.0986] [13], [incidence rate ratio = 0.81, 95% CI: 0.65, 099] p = 0.046) and in adults (1072 elderly, reduced the mean duration of CID episode to 6.5 versus 8 days, p = 0.008) [54]. The latter author published another study in adults, reporting that daily consumption of a fermented dairy product containing L. casei DN-114 001 could reduce the risk of common infections in stressed individuals such as shift workers (OR = 0.75, 95% CI 0.59 --0.95, p = 0.017) [55]. The reduction in the incidence and duration of CID episodes at different ages suggested that this strain is effective throughout the lifetime, which might not be the case with other strains and different probiotics, since it is well known that human microbiota change with age, diet and chronic disease [56,57].…”
Section: Ref Outcomes (Probiotic Vs Control)mentioning
confidence: 99%
“…Double-blind RCTs (DBRCTs) of this strain reported beneficial effects both in children (638 children, 3 --6 years old in daycare/schools, the incidence rate for CIDs in probiotic group [0.0782] was 19% lower than the control group [0.0986] [13], [incidence rate ratio = 0.81, 95% CI: 0.65, 099] p = 0.046) and in adults (1072 elderly, reduced the mean duration of CID episode to 6.5 versus 8 days, p = 0.008) [54]. The latter author published another study in adults, reporting that daily consumption of a fermented dairy product containing L. casei DN-114 001 could reduce the risk of common infections in stressed individuals such as shift workers (OR = 0.75, 95% CI 0.59 --0.95, p = 0.017) [55]. The reduction in the incidence and duration of CID episodes at different ages suggested that this strain is effective throughout the lifetime, which might not be the case with other strains and different probiotics, since it is well known that human microbiota change with age, diet and chronic disease [56,57].…”
Section: Ref Outcomes (Probiotic Vs Control)mentioning
confidence: 99%
“…This was one of the most well studied strains in the food supply with eleven studies, all funded by Danone, investigating its effects [35]. Three studies showed decreased incidence [26,35] and duration [36] of common infectious diseases (ranging from upper respiratory tract infections to sore throats and influenza) in adults, children, and seniors. Of these, one study showed decreased duration of acute diarrhea in children [31].…”
Section: Resultsmentioning
confidence: 99%
“…The score, however, was rather high at baseline that may have limited the sensitivity for detecting alterations when compared with other studies with the same product tested in adult stressed populations (35,36). The safety profile of the active product was good, with <5% of volunteers experiencing only moderate to mild adverse events.…”
Section: Discussionmentioning
confidence: 58%
“…There were only few missing data because of premature withdrawal, and they were balanced in numbers across the 2 groups with similar reasons for missing data. This makes reasons for missing data unlikely to be related to true outcome and unlikely to have a clinically relevant impact on the intervention effect estimate indicating low risk of attrition bias according to the Cochrane Collaboration (35). The 3 remaining subjects with major protocol deviations had problems with compliance; these subjects withdrew prematurely from the study: 1 subject presented with a clinically significant abnormality at the clinical examination at V1, 1 subject had a serious adverse event during product consumption, and 1 subject did not respect the visit window between V4 and V5.…”
Section: Resultsmentioning
confidence: 99%